Evaluasi Tingkat Pengetahuan dan Kepatuhan Pasien Tuberkulosis Paru di Puskesmas Rancabali - Syifa Egidia Delani; Umi Yuniarni; Lanny Mulqie (UNISBA Press, 2022)
Abstract. Tuberculosis (TB) is an infectious disease that is still a major health problem in Indonesia because it has a major impact on the decline in work productivity. The purpose of this study was to determine the effect of the level of patient compliance on the success of pulmonary tuberculosis therapy. This study used descriptive survey method, and the data was collected by prospective method. In this study, there are 3 (three) forms of questionnaire, which are demographic data, the level of knowledge, and the level of adherence. This study has been done from April-May 2022. The subject who involved in this study are patients with pulmonary tuberculosis at Pulmonary Polyclinic General Puskesmas Rancabali. The assessments of the adherence level was done using MMAS (Morisky Medication Adherence Scale) questionnaire and knowledge level assessment using a general knowledge questionnaire about pulmonary TB. The result of 50 patients which fulfilled in inclusion criteria showed that the majority of patient’s age was 26-35 years which was 21 people (42%), the majority of gender was men which was 26 people (61%), the majority of high school student which was 20 people (40%), the majority of government officers which was 21 people (42%). The result shows mayoity the compliance of pulmonary tuberculosis treatment is good (46%). The level of knowledge about the complience therapy in the patients are in good category 30 people (60%). The result of statistical analysis showed that there was a relationship between patient knowledge and compliance in carrying out pulmonary TB treatment at Puskesmas Rancabali (p = 0.007) Abstrak. Tuberkulosis (TB) merupakan penyakit menular yang masih menjadi masalah kesehatan utama di Indonesia karena berpengaruh besar terhadap penurunan produksitivitas kerja. Tujuan dari penelitian ini adalah untuk megetahui pengaruh tingkat kepatuhan pasien terhadap keberhasilan terapi Tuberkulosis Paru. Penelitian ini menggunakan metode deskriptif, pengambilan data dilakukan secara prospective. Dalam penelitian ini terdiri dari 3 (tiga) bentuk kuisioner yaitu data demografi, tingkat pengetahuan, dan tingkat kepatuhan. Penelitian dilakukan pada bulan April-Mei 2022. Subjek yang terlibat dalam penelitian ini adalah pasien tuberkulosis paru di Poli TB Puskesmas Rancabali. Penilaian tingkat kepatuhan menggunakan kuesioner MMAS (Morisky Medication Adherence Scale) dan penilaian tingkat pengetahuan menggunakan kuisioner pengetahuan umum tentang TB Paru. Hasil dari 50 pasien yang memenuhi kriteria inklusi menunjukkan bahwa mayoritas pasien TB Paru adalah berusia 26-35 tahun sebanyak 21 orang (42%), jenis kelamin laki-laki sebanyak 26 orang (52%), pendidikan SMA/Sederajat sebanyak 20 orang (40%), pekerjaan pegawai swasta sebanyak 21 orang (42%). Berdasarkan hasil kepatuhan menunjukkan bahwa mayoritas tingkat kepatuhan pasien tuberkulosis paru adalah baik (46%). Penilaian tingkat pengetahuan pasien dengan kategori baik sebanyak 30 orang (60%). Hasil uji statistik menunjukkan adanya hubungan antara pengetahuan pasien dengan kepatuhan dalam menjalankan pengobatan TB Paru di Puskesmas Rancabali (p=0,007).